Producing Trans economicus: Deploying Market Logic in the Fight for Trans Rights - Vipond, Evan (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
This article analyzes how market logic is deployed to secure trans rights under neoliberalism in Canada and the U.S. I argue that by embodying the ‘ideal’ neoliberal subject, productive trans persons are granted access to state institutions and social services, including transition-related medical care. This is achieved through the accumulation of what Foucault (2008) calls “human capital” and appealing to market logic (cost-benefit analysis). While doing so may afford certain trans people – namely white, affluent, and able-bodied – increased access to services and material success, it ultimately reinforces neoliberal logic, further obscuring and exacerbating social and economic inequalities. I argue that trans persons who achieve material success are upheld as ‘proof’ that neoliberalism functions as a meritocracy, shifting the burden of social and economic responsibility away from the state and onto the individual.